Influence of training loads on the change special of performance of skiers - Chernyaev, A. A.; Fonareva, E. A.; Bikushev, R. R. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
Training of skiers-racers of high qualification, at the present stage, is associated mainly with the improvement of the training process, brought into line with the biological laws of the course of adaptation processes. Priority should be given to the main parameters of training and competitive loads on the basis of the expected structure of the competitive activity and the planned sports result. Many athletes often ask questions, how justified are these or those coaching received trainings, why, it is often, despite significant volume of training loads, the sports results are not only improving, and there is trend to their decline. In the first part, the laboratory study was conducted to assess the relationship between volume and intensity. Testing was carried out (OFP and standard loads) during which the subjects were divided into two groups. In the second part, the training effects of physical activity with a different ratio of volume, intensity and direction were evaluated. As a criterion, the specific working capacity has been taken, which was estimated both on special, and on competitive exercises.